Growth differentiation factor-15 prevents glucotoxicity and connexin-36 downregulation in pancreatic beta-cells. (5th February 2022) - Asrih, Mohamed; Dusaulcy, Rodolphe; Gosmain, Yvan; Philippe, Jacques; Somm, Emmanuel; Jornayvaz, François R.; Kang, Baeki E.; Jo, Yunju; Choi, Min Jeong; Yi, Hyon-Seung; Ryu, Dongryeol; Gariani, Karim
Abstract: Pancreatic beta cell dysfunction is a hallmark of type 2 diabetes. Growth differentiation factor 15 (GDF15), which is an energy homeostasis regulator, has been shown to improve several metabolic parameters in the context of diabetes. However, its effects on pancreatic beta-cell remain to be identified. We, therefore, performed experiments using cell models and histological sectioning of wild-type and knock-out GDF15 mice to determine the effect of GDF15 on insulin secretion and cell viability. A bioinformatics analysis was performed to identify GDF15-correlated genes. GDF15 prevents glucotoxicity-mediated altered glucose-stimulated insulin secretion (GSIS) and connexin-36 downregulation. Inhibition of endogenous GDF15 reduced GSIS in cultured mouse beta-cells under standard conditions while it had no impact on GSIS in cells exposed to glucolipotoxicity, which is a diabetogenic condition. Furthermore, this inhibition exacerbated glucolipotoxicity-reduced cell survival. This suggests that endogenous GDF15 in beta-cell is required for cell survival but not GSIS in the context of glucolipotoxicity. Highlights: High glucose and palmitate treatment increase GDF15 in cultured pancreatic beta-cells and INS-1E cells. GDF15 prevents glucose-stimulated insulin secretion inhibited by glucolipotoxicity in the beta-cell and INS-1E cells. GDF15 prevent glucotoxicity induced connexin-36 downregulation in INS-1E cells. GDF15 is a potential therapeutic agent which can delay the need of insulin under glucolipotoxic conditions.